2020
DOI: 10.1007/s00268-020-05735-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Postoperative Pancreatic Fistula—A Swedish Nationwide Register‐Based Study

Abstract: Background A serious complication after pancreatoduodenectomy (PD) is postoperative pancreatic fistula (POPF). The aim of this study was to analyse the incidence and predictive factors for POPF by using a large nationwide cohort. Methods Data from the Swedish National Registry for Pancreatic and Periampullary Cancer for all patients undergoing a PD from 2010 until 30th June 2018 were collected. The material was analysed in two groups, no POPF and clinically relevant (grade B and C) POPF. Results A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 52 publications
0
27
0
10
Order By: Relevance
“…In a retrospective study using Swedish national data, Williamsson et al (n = 2503) found incidence of CR-POPF was 10.0%; this correlated with major morbidity (75% versus 21%, p < 0.001) and longer length of stay (23 versus 11 p < 0.001). 6 Obesity (OR 1.08, p < 0.001) was a risk factor, whereas diabetes (OR 0.58, p = 0.012) and preoperative biliary drainage (OR 0.34, p < 0.001) were protective. 6 CR-POPF was significantly more likely in patients who underwent pancreatojejunostomy (PJ) compared with pancreatogastrostomy (PG, OR 2.41, p < 0.001).…”
Section: Pancreatic Fistulamentioning
confidence: 95%
“…In a retrospective study using Swedish national data, Williamsson et al (n = 2503) found incidence of CR-POPF was 10.0%; this correlated with major morbidity (75% versus 21%, p < 0.001) and longer length of stay (23 versus 11 p < 0.001). 6 Obesity (OR 1.08, p < 0.001) was a risk factor, whereas diabetes (OR 0.58, p = 0.012) and preoperative biliary drainage (OR 0.34, p < 0.001) were protective. 6 CR-POPF was significantly more likely in patients who underwent pancreatojejunostomy (PJ) compared with pancreatogastrostomy (PG, OR 2.41, p < 0.001).…”
Section: Pancreatic Fistulamentioning
confidence: 95%
“…Braga[56] considered that the increase in BMI, the presence of fatty pancreas and pancreatic brosis were the risk factors for pancreatic stula after surgery, and based on these three factors, pancreatic stula could be scored and predicted, and then preventive measures could be formulated. It has been reported in the literature that total pancreatic fat in patients with diabetes is signi cantly reduced and brosis aggravates, which actually plays a protective role for patients with POPF [57]. A univariate and multivariate regression analysis of BMI in 175 patients in this retrospective study revealed that BMI was an independent risk factor for pancreatic stula.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, most patients undergoing PD prior to 2017 had ampullary tumors (53.5%), while most patients undergoing PD after 2017 had pancreatic head tumors (68.2%). A previous study reported that pancreatic head tumors had signi cantly decreased incidences of POPF, which may be due to the parameters associated with in ammation of the parenchyma or obstruction of the pancreatic duct leading to pancreatic rmness [18]. However, a soft pancreas has been associated with fatty in ltration.…”
Section: Discussionmentioning
confidence: 96%